Customer Orientation, Channel Member Relationship and Company Performance – The Mediating Effect of Contractor-Supplier Commitment in the Construction Industry - Mohtar, Noorhanaliza; Abd Rahman, Sofiah (International Journal of Supply Chain Management, 2020)
Construction is a major industry throughout the world which is not only related to its size but also to its role in economic growth.  While its contribution to nation-building is significant, in practice, the industry is still typically managed along traditional lines, within a complex and yet fragmented network of the supply chain. As a result, evidences have shown that the construction industry has not been keeping pace with the rest of the economy. Building from the marketing perspective, this paper argued that performance is very much linked to the practice of becoming customer oriented, building relationship among channel partners and exhibiting strong commitment. This study, thus, examined these relationships in a more coherent and integrated approach from the construction industry supply chain in Malaysia. The objective is to establish an association between these constructs and their dimensions on this linkage. The quantitative method was used to test the relationship between the four constructs. The analysis was conducted using Partial Least Square (PLS) technique. The findings revealed that Customer Orientation and Channel Member Relationship have positive effects on Company Performance and Contractor-Supplier Commitment mediates the relationship between Customer Orientation, Channel Member Relationship and Company Performance. Future study should explore more on this to gain better insights which could add another body of knowledge in the construction industry and further propel the Malaysian CI contribution to GDP.